The Role of Character Education in Shaping an Excellent Generation in the Era of Globalization - Adit Tiro; Rosi Andani; Kasmantoni Kasmantoni; Adam Nasution (The Future of Education Journal, 2026)
This study aims to analyze the role of character education in shaping an excellent generation in the era of globalization, which is marked by rapid technological development and the swift flow of information. The research employs a qualitative approach using a literature study method by examining various scholarly sources such as journals, books, and documents related to character education. The findings indicate that character education plays a crucial role in developing a generation that is not only intellectually competent but also possesses strong moral values, ethics, and personality. The implementation of character education can be carried out through integration into the curriculum, habituation in daily school life, and role modeling by teachers and the surrounding environment. Thus, character education serves as a fundamental foundation in addressing the challenges of globalization, enabling the younger generation to compete globally without losing their identity and noble cultural values.